STRATEGIC PLANNING AND POLITICAL DYNAMICS IN THE MANAGEMENT OF VILLAGE-OWNED ENTERPRISES (BUMDESA) IN TASIKMALAYA REGENCY 2022-2024 - Sutrisno, Beni; A.D, H. Nandang; Yuningsih, Neneng Yani (Universitas Padjadjaran, 2025)
Strategic Planning and Political Dynamics in the Management of BUMDesa in Tasikmalaya Regency, 2022-2024: A Case Study of BUMDesa Warga Saluyu in Sukaluyu Village, Mangunreja Subdistrict, and BUMDesa Walatra in Salawu Village, Salawu Subdistrict, Tasikmalaya Regency, examines how strategic planning is implemented in BUMDesa Warga Saluyu and BUMDesa Walatra, as well as how local political dynamics influence the implementation of policies. This research uses a qualitative method with a case study approach to analyze strategic planning and political dynamics in the management of BUMDesa, combining primary data from in-depth interviews and field observations with secondary data from media documentation and previous studies. The findings show that strategic planning in the management of BUMDesa in Tasikmalaya Regency, such as in BUMDesa Warga Saluyu and BUMDesa Walatra, is directed toward the development of local potential, particularly in the fields of tourism and agriculture. However, challenges include limited resources and local political dynamics that affect policy and program implementation. Based on Lorange’s theory in Bryson regarding Mission, Strategy, Budget, and Control, this study emphasizes the need for a comprehensive approach to strategic planning and the management of BUMDesa in Tasikmalaya Regency. Furthermore, the analysis also considers the implications of local political dynamics and the role of regional governments and communities in managing BUMDesa. Overall, this research provides valuable insights into the capacity of BUMDesa Warga Saluyu and BUMDesa Walatra in implementing strategic planning, highlighting the importance of effective collaboration and coordination among stakeholders to improve community welfare and promote sustainable village development.